Electrocatalytic hydrogen evolution using metal-free porphyrins. (11th October 2018) - Manton, Jennifer C.; Hidalgo, Diana; Frayne, Liam; Brandon, Michael P.; Vos, Johannes G.; Pryce, Mary T.
Abstract: The direct deposition of metal-free porphyrins onto carbon electrodes to conveniently form hydrogen production cathodes is reported for the first time. It is revealed that the rate of hydrogen generation can be optimised by adding appropriate substituents to the tetraphenyl-porphyrin (TPP) molecule, with electron donating groups enhancing performance. Excellent electrocatalytic behaviour is evident with a Faradaic efficiency of about 90%. Turn over numbers (TON) of up to 100, 000 for TPP and 250, 000 for Methoxy-TPP are observed after 1 h of electrolysis. These electrodes are stable for at least 6 h and can be re-used several times without reducing the TONs and Faradaic efficiency. The influence of substituents is discussed in terms of a scenario where the discharge of a hydronium ion by a ring nitrogen atom is apparently rate determining. This work reveals that metal-free macrocycles can be tuned to promote electrochemical water splitting, with the potential to offer cost-effective and sustainable alternatives to precious metal based electrocatalysts. Highlights: Tetraphenylporphyrin (TPP) was prepared and meso-substituted with different groups. Films of these metal-free porphyrins were drop-cast on glassy carbon electrodes. Methoxy-TPP exhibited the best electrocatalytic activity for Hydrogen production. The electronic character of the substituted groups influenced catalytic performance. Electron donating groups may promote the discharge of a proton from solution.